Síntese e avaliação termo-oxidativa de potenciais biolubrificantes a partir do cardanol - Almeida, Mayara Oliveira de (2017)
The need to replace petroleum based lubricants with sustainable and environmentally friendly alternatives has encouraged the development of vegetable oil based materials - Biolubricants. Although there are several advantages, the development of biolubricants can compete directly with the agricultural and food sector, making their use unfeasible with respect to economic and social aspects. The present work describes the use of cardanol, a major constituent of an agro-industrial by-product obtained from cashew nut shell liquid (CNSL), as a raw material in the synthesis of new compounds as potential biolubricants. The synthesis of these materials was carried out under solvent free conditions, free of catalyst and/or using microwave irradiation. The biolubricants obtained were structurally characterized by techniques mass spectrometry (GC/MS), infrared (IR) spectroscopy and NMR (1H and 13C). The thermal and oxidative stability of the materials were also evaluated by the thermoanalytical techniques, TGA and DSC. And their viscosities were analyzed by means of rheological studies. The TGA results showed that the chemical modifications in the cardanol led to the obtaining of compounds with high thermo-oxidative stability, which presented values of T (onset) above 220 ° C. The DSC analysis (ASTM E-2009) showed that all products obtained had a much higher initial oxidation temperature (OOT) than cardanol. The rheological studies indicated that the different chemical modifications also influenced the viscosities of the potential biolubricants.